Factors Facilitating Teacher’s Professional Competence Development - Alyona Shyba (Linguaculture, 2019)
The objective of the article is to further study the concept “teacher’s professional competence” as well the ways of its formation. The research was conducted among the students as prospective teachers, and teaching staff of Yuriy Fedkovych Chernivtsi National University. The analysis of the research helped prove the essential role of some factors in the professional development of future teachers. In particular, such factors as knowledge of the teaching subject, knowledge of effective teaching methods and skills to implement them, the importance of teaching practice, the personality factor, teacher’s self-education were singled out. Therefore, the paper aims to outline a few ideas on how to ensure the implementation of the above-mentioned considerations. We also dwell upon the impact of the human behavior on the process of foreign language learning and teaching. That is why knowledge about affective factors is consequential in the academic process and using some interactive methods can also help lower the affective filter. Types of motivation and ways to enhance it are described in the paper too.